Optimized Rectenna Design for Wireless Power Transfer in Implantable Systems - Islam, Akib Jayed; Salehin, Sultanus; Pranta, Swapnil; Barua, Nirzar; Pavel, Tanvir A.; Uddin, Arafat; Ananna, Kaniz Fatema (Devices for Integrated Circuit, 2025)
The integration of radio frequency (RF)-based wireless power transfer (WPT) systems into implantable medical devices (IMDs) represents a transformative step toward realizing fully autonomous, battery-free biomedical implants. This study presents the design, simulation, and optimization of a miniaturized implantable rectenna operating at the 2.4 GHz ISM band, aimed at addressing the critical challenges of power delivery, biocompatibility, and electromagnetic safety. A multi-layered human tissue phantom model incorporating realistic dielectric properties is developed to assess in-situ antenna performance and ensure compliance with specific absorption rate (SAR) regulations. The antenna is geometrically optimized for low return loss, minimal volume, and efficient power harvesting under physiological constraints. Concurrently, the rectifier circuit is designed using harmonic balance analysis in ADS, with various diode models evaluated for maximizing RF-to-DC conversion efficiency. The proposed system achieves a peak efficiency of 88.65%, with SAR values maintained well below regulatory limits across multiple implant positions. These findings underscore the potential of the proposed rectenna architecture to enable safe and efficient wireless powering of next-generation IMDs, thereby advancing the frontier of biomedical telemetry and implantable electronics.